EVALUASI KINERJA BADAN USAHA MILIK DESA DALAM PENINGKATAN EKONOM MASYARAKAT DI DESA SILALAHI I, KECAMATAN SILAHISABUNGAN - Matanari, Gabe Pos; Pasaribu, Jhonson; Lumbanraja, Riana (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This study aims to determine the performance of BUMDes which was established in 2022 based on Village Regulation Number 6 of 2014 concerning BUMDes. This study uses a qualitative research method with a descriptive analysis approach. BUMDes is a village-owned economic body or institution established by the village government to advance the village economy and improve the welfare of the community in accordance with Permendes no. 6 of 2018. Performance evaluation criteria according to Laster and Stiwert (2020) 6 evaluation criteria according to Laster and Stiwert, namely, Relevance, efficiency, effectiveness, learning and impact. The results of the study indicate that the BUMDes Silalahi I program is relevant to be implemented in Silalahi I Village, but in its implementation there is still a lack of relevance between the program and the government, then the lack of effectiveness in the BUMDes program, causing obstacles in implementing the program in assessing BUMDes performance, lack of good cooperation between BUMDes and the community.